2012
DOI: 10.3415/vcot-12-01-0002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of external coaptation on plate deformation in an ex vivo model of canine pancarpal arthrodesis

Abstract: The application of a cast to the distal portion of the limb significantly reduced strain in the 2.7/3.5 mm hybrid PCA plate, but the magnitude of the measured strain was low, suggesting that fatigue damage is unlikely to accumulate as a result of this type of loading and that external coaptation may not be necessary to prevent fatigue failure of the plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While an ex vivo mechanical study of pancarpal arthrodesis (PCA) constructs provided evidence that the use of a cast significantly reduced plate strain, the strain magnitude was low and considered unlikely to be clinically significant. 11 This ex vivo finding would appear to be supported by the results of a retrospective study on PCA in which it was concluded that external coaptation had no measurable benefit. 12 From a mechanical perspective in PTA, medial plating allows "edge" loading of the implant, and, compared to dorsal plating, increases the dorsoplantar bending stiffness of the construct.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…While an ex vivo mechanical study of pancarpal arthrodesis (PCA) constructs provided evidence that the use of a cast significantly reduced plate strain, the strain magnitude was low and considered unlikely to be clinically significant. 11 This ex vivo finding would appear to be supported by the results of a retrospective study on PCA in which it was concluded that external coaptation had no measurable benefit. 12 From a mechanical perspective in PTA, medial plating allows "edge" loading of the implant, and, compared to dorsal plating, increases the dorsoplantar bending stiffness of the construct.…”
Section: Introductionmentioning
confidence: 83%
“…External coaptation has been advocated to provide adjunctive stability after arthrodesis with internal fixation, 18,19 although the effectiveness of coaptation in reducing loading of the implants remains unclear. In an ex vivo study on PCA, Woods et al 11 found that, although the application of a cast to the distal portion of the limb significantly reduced strain in a 2.7/3.5-mm hybrid PCA plate, the magnitude of the measured strain was low. This provided evidence that fatigue damage was unlikely to accumulate as a result of this type of loading and that external coaptation may not be required to prevent fatigue failure of the plate.…”
Section: Discussionmentioning
confidence: 99%